Frog on a log? - Gray, Kes,Field, Jim (Scholastic Press, 2015)
In rhyming text, cat explains why frog has to sit on a log, even if he finds it uncomfortable
Keywords: Bilderbuch; Frogs; Cats; Stories in rhyme; Animals